The Vanishing Barter Economy in Russia: A Test of the Virtual Economy Hypothesis? Reply to Barry Ickes - Dalia Marin (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
This paper is a reply to Barry Ickes' critique of my paper 'Trust versus Illusion: What is Driving Demonetization in Russia?' in which I show that the data reject Barry Ickes' Virtual Economy explanation of barter in Russia in favor of an institutional explanation based on the lack of trust.
urn:nbn:de:bvb:19-epub-13468-8
Keywords: D20; G30; O10; P30; 330; imperfect input and capital markets; the virtual economy; trade credit; trust; contract enforcement